2015
DOI: 10.1186/s13041-015-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of fast astrocytic component in voltage-sensitive dye imaging of neural activity

Abstract: BackgroundVoltage-sensitive dye (VSD) imaging and intrinsic optical signals (IOS) are widely used methods for monitoring spatiotemporal neural activity in extensive networks. In spite of that, identification of their major cellular and molecular components has not been concluded so far.ResultsWe addressed these issues by imaging spatiotemporal spreading of IOS and VSD transients initiated by Schaffer collateral stimulation in rat hippocampal slices with temporal resolution comparable to standard field potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 123 publications
(128 reference statements)
0
8
1
Order By: Relevance
“…3O). In contrast to previous reports [1623], we found no contribution of glutamate transporters (Fig. 4F and 4G) and the apparent contribution upon long-term treatment by inhibitors such as DHK and TBOA was due to an undesirable sideeffect such as desensitization of postsynaptic glutamate receptors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…3O). In contrast to previous reports [1623], we found no contribution of glutamate transporters (Fig. 4F and 4G) and the apparent contribution upon long-term treatment by inhibitors such as DHK and TBOA was due to an undesirable sideeffect such as desensitization of postsynaptic glutamate receptors.…”
Section: Discussioncontrasting
confidence: 99%
“…Astrocytes rapidly take-up glutamate resulting from presynaptic glutamate release during synaptic transmission via glutamate transporters, mostly expressed in astrocytes [22]. Recently, the astrocytic glutamate transporter EAAT2 has been reported to contribute to IOS as evidenced by a significant inhibition of IOS by dihydrokainic acid (DHK), an inhibitor for glutamate transporter EAAT2 [1623]. However, a long-term treatment with glutamate transporter inhibitors could cause an undesirable side-effects such as desensitization of glutamate receptors such as AMPA, kainate, and NMDA receptors by accumulated glutamate at the synaptic junctions, giving rise to a misinterpretation of the results.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, wide-field VSD imaging approaches were used to determine if the cellular defects in 3xTg-AD mice translate to abnormal signal propagation across subfields of the Schaffer collateral - CA1 network [9597]. Although neural activity and glial responses contribute to VSD signals [98], VSD imaging is a powerful technique to monitor circuit activity across brain networks. In AD mouse models, VSD imaging has previously been used to examine signaling in the dentate gyrus [99], but to our knowledge, this is the first VSD study to examine AD-related CA1 network deficits in concert with electrophysiological and Ca 2+ responses.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this view, Cajal further revealed that “the neuroglia is abundant where intercellular connections are numerous and complicated, not due to the existence of contacts, but rather to regulate and control them, in such a manner that each protoplasmic expansion is in an intimate relationship with only a particular group of nerve terminal branches”, which led him to propose that astrocytes exert a major role in modulating brain function during different behavioral states (Cajal, 1895, 1897). More than a century later, with the development of powerful electrophysiological and imaging tools (Berger et al, 2007; Pál et al, 2015), these initial insights about astrocytes as potential modulators of the brain circuitry are gaining more support.…”
Section: Discussionmentioning
confidence: 99%